Early Tracheostomy in Adult Patient with Head Trauma: A Case Report - Abdullah, Adnan; Arrifqi, Faiyana Nurul; Firmansyah, Rizky; Daniswara, Deoni (Ahmad Dahlan Medical Journal, 2025)
Traumatic brain injury (TBI) is a serious condition that can cause temporary or permanent physical, cognitive, and emotional impairments. Tracheostomy in TBI patients can help reduce airway resistance, improve secretion clearance, and support weaning from mechanical ventilation. Early tracheostomy (ET) may also reduce ICU stay, ventilation time, and long-term mortality. A 30-yearold female was referred after a motorbike accident without a helmet. She was unconscious, with a Glasgow Coma Scale (GCS) of E1V2M1. Vital signs: temperature 38.1°C, pulse 74/min, respiratory rate 25/min, blood pressure 84/47 mmHg. Eye examination revealed lagophthalmos, chemosis, and a corneal epithelial defect. Neurological findings included anisocoria (right pupil 5 mm, left 3 mm), with no response in cranial nerves III, IV, and VI. Reflexes were normal, and no neck stiffness was observed. CT scan showed subdural hematoma (SDH), subarachnoid hemorrhage (SAH), and intracerebral hemorrhage (ICH). The patient underwent tracheostomy, central venous catheter placement, craniotomy, decompression, and hematoma evacuation. The bleeding volume was 15 cc. She survived and regained consciousness (GCS compos mentis). This case highlights the potential benefit of early tracheostomy in severe TBI. While patients with more severe injuries may face delays due to instability, early intervention can support better outcomes and survival.